Diagnostic and treatment principles of wound process in patients with diabetic foot syndrome and risk groups. Draft recommendations - A. A. Supilnikov; E. V. Kolesnikov; A. A. Starostina; L. A. Trusova; M. S. Mikhailov; S. A. Mantsagova; B. I. Yaremin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The draft clinical guidelines were developed by the team of the scientific group for the treatment of wounds and wound process of the Reaviz Medical University, taking into account modern scientific data, practical experience and original research. The data on the formulation of the diagnosis in diabetic foot syndrome, the existing classification of ulcers and wounds, the survey plan, basic and additional therapy, local treatment of ulcers and wounds are presented.